DETERMINASI KINERJA AUDITOR INTERNAL PEMERINTAH : SURVEI PADA APIP KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN - Paulus Dwi Arde Nugroho (2022)
This study aims to determine the effect of use of CAAT, self-efficacy, and work motivation on auditor performance. The population of this study are internal auditors who work at the Inspectorate General of the Ministry of Education and Culture. This study used probability sampling method and obtained 86 internal auditors as respondents. This type of research is quantitative research. The research data were analyzed using the SEM-PLS method using a significance level of 10% (0.10). The results showed that the use of CAAT, self-efficacy, and work motivation had a partially positive significant effect on auditor performance. Keywords: Use of CAAT, Self Efficacy, Work Motivation, dan Auditor's Performances